A NASICON-type solid-state electrolyte, a positive electrode material, and a preparation method and application thereof

CN116799291BActive Publication Date: 2026-11-03NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310788836.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2026-11-03
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

The existing NASICON-type solid electrolyte has severe electronic insulation that hinders electron transport, leading to increased charge transfer resistance and interfacial impedance of the cathode material, which limits the capacity utilization of the cathode material and the electrochemical performance of the battery.

Method used

By introducing transition metal elements M1 and M2, an M1O6 octahedral structure and M2O4a-covalent chemical bonds are formed, which replace some of the PO43- chemical bonds, thereby improving the electronic conductivity of the solid electrolyte. Furthermore, by limiting the proportion of P replaced by M2, the electrolyte acquires dual conduction properties of lithium-ion conduction and electronic conduction.

Benefits of technology

A NASICON-type solid electrolyte with high electronic conductivity was achieved, and a lithium-ion-electron dual transport network was constructed, which improved the battery's specific capacity, rate performance, and cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116799291B_ABST
    Figure CN116799291B_ABST
Patent Text Reader

Abstract

The application provides a NASICON type solid electrolyte, a positive electrode material and a preparation method and application thereof, and the chemical structural formula of the NASICON type solid electrolyte is as follows: Li 1+x M 1 x Ti 2‑x (PO4) y (M 2 O4) z , wherein 0<=x<=0.6, 1.5<=z<=4.5, 50%<=z / (y+z)<=100%; M 1 comprises at least one of Al, Y, Fe, Cr, Nb and Zr; M 2 comprises at least one of V, Mo, W and Nb. By introducing transition metal elements and limiting the proportion of the transition metal elements, the electronic conductivity of the solid electrolyte is maximized, so that the solid electrolyte has the dual conduction properties of lithium ion conduction and electronic conduction. The ternary lithium ion battery positive electrode material coated by the coating modification of the NASICON type with the electronic-ion dual conduction property provided by the application can simultaneously conduct lithium ions and electrons, and the electrical performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a NASICON-type solid electrolyte, a cathode material, its preparation method, and its application. Background Technology

[0002] The cathode is a crucial component of lithium-ion batteries. Coating the surface of the cathode material with a solid electrolyte material can effectively improve its thermal stability, specific capacity, and lithium-ion conductivity. Currently, phosphate polyanionic (NASICON-type) solid electrolytes exhibit high lithium-ion conductivity (>10). -4 With advantages such as high S / cm and a high electrochemical window (>4.3V), NASICON-type solid electrolytes are widely used for coating the surface of cathode materials. For example, patent documents CN115513437A, CN111600014B, and CN115425202A disclose the coating of high-nickel ternary cathode materials with NASICON-type solid electrolytes. While this can promote lithium-ion transport to some extent, in actual battery systems, the cathode needs not only to construct a lithium-ion transport network but also to establish a good electron transport network. Due to the inherent electronic insulation properties of NASICON-type solid electrolytes (electronic conductivity typically <10), this method is less effective. -8 The S / cm coating layer on the surface of the ternary cathode material severely hinders electron transport, resulting in a large charge transfer resistance, which increases the powder impedance of the cathode material. This restricts the construction of the electron transport network, increases the interfacial impedance of the cathode sheet, and makes it difficult for the cathode material to effectively realize its theoretical capacity. It also increases the polarization and internal resistance of the battery, thus restricting the capacity utilization and electrochemical performance of the battery.

[0003] Currently, most methods to improve the electronic conductivity of NASICON-type solid electrolytes involve doping with elements, such as Neelakshi Sharma et al. in their paper "Vanadium substituted Li + The journal *NASICON Systems: Tailoring Electronic Conductivity for Electrode Applications* (Journal of Alloys and Compounds) discloses the application of LiTi2(PO4)3(LTP) and Li 1.3 Al 0.3 Ti 1.7 Partial VO4 in the Nasicon structure of (PO4)3(LATP) material 3- Replacement part of PO4 3- LiTi2(PO4) was obtained respectively. 3-x (VO4)x and Li 1.3 Al 0.3 Ti 1.7 (PO4) 3-x (VO4) x (x = 0.1~0.4), but the improvement in electronic conductivity of NASICON-type solid electrolytes achieved by the above methods falls far short of the required level. Therefore, how to obtain NASICON-type solid electrolytes with high electronic conductivity has been a long-standing research topic in this field. Summary of the Invention

[0004] This invention provides a NASICON-type solid electrolyte that, by introducing transition metal elements and limiting their proportion, maximizes the electronic conductivity of the solid electrolyte, enabling it to possess dual conduction properties of lithium-ion conduction and electronic conduction.

[0005] The present invention also provides a method for preparing a NASICON-type solid electrolyte, which can produce the above-mentioned NASICON-type solid electrolyte, which has both high electronic conductivity and high lithium-ion conductivity.

[0006] The present invention also provides a cathode material that, by coating the above-mentioned NASICON-type solid electrolyte, facilitates the construction of a lithium-ion-electron dual transport network, enhances the reaction kinetics of ion / electron exchange, and helps to improve rate performance and cycle performance while ensuring battery specific capacity.

[0007] The present invention also provides a method for preparing a positive electrode material, which can produce the above-mentioned positive electrode material. Applying the positive electrode material to a battery can help improve the battery's specific capacity, rate performance and cycle performance.

[0008] The present invention also provides a positive electrode sheet, which, by including the above-mentioned positive electrode material, is beneficial to improving the specific capacity, rate performance and cycle performance of the battery when applied to a battery.

[0009] The present invention also provides a battery that, due to including the above-mentioned positive electrode, has both high specific capacity, excellent rate performance and cycle performance.

[0010] In a first aspect, the present invention provides a NASICON-type solid electrolyte, wherein the chemical structural formula of the NASICON-type solid electrolyte is: Li 1+x M 1 x Ti 2-x (PO4) y (M 2 O4) zWhere 0≤x≤0.6, 1.5≤z≤4.5, and 50%≤z / (y+z)≤100%;

[0011] M 1 Including at least one of Al, Y, Fe, Cr, Nb, and Zr; M 2 It includes at least one of V, Mo, W, and Nb.

[0012] The NASICON-type solid electrolyte described above, wherein the electronic conductivity of the NASICON-type solid electrolyte is >10. -5 S / cm; and / or,

[0013] The lithium-ion conductivity of the NASICON-type solid electrolyte is >10. -4 S / cm; and / or,

[0014] The band gap of the NASICON-type solid electrolyte is no greater than 0.7 eV.

[0015] A second aspect of the present invention provides a method for preparing the NASICON-type solid electrolyte described in the first aspect, comprising the following steps: mixing a lithium source, a titanium source, a phosphorus source, and providing M... 1 Compounds that provide M 2 The compounds were mixed and sintered to obtain a NASICON-type solid electrolyte.

[0016] In the preparation method described above, the sintering treatment is a one-stage sintering, wherein the temperature of the one-stage sintering is 650–1050℃ and the time is 2–10 h; or,

[0017] The sintering process is a two-stage sintering process, which includes a first sintering process and a second sintering process. The temperature of the first sintering process is 450-550℃, and the temperature of the second sintering process is 800-1000℃.

[0018] A third aspect of the present invention provides a positive electrode material, comprising a positive electrode material matrix and a coating layer covering the surface of the positive electrode material matrix, wherein the material of the coating layer comprises the NASICON-type solid electrolyte described in the first aspect or a NASICON-type solid electrolyte prepared by the preparation method described in the second aspect.

[0019] In the cathode material described above, the NASICON-type solid electrolyte accounts for 0.01 to 5 wt% of the cathode material matrix.

[0020] A fourth aspect of the present invention provides a method for preparing the positive electrode material described in the third aspect, comprising the following steps: pulverizing a NASICON-type solid electrolyte to obtain nanoparticle powder; mixing the nanoparticle powder or a slurry formed from the nanoparticle powder with a positive electrode material matrix and then annealing the mixture to obtain the positive electrode material.

[0021] In the preparation method described above, the annealing treatment is carried out in an oxygen-containing atmosphere at a temperature of 250–800°C for 2–15 hours; and / or,

[0022] The D50 of nanoparticle powder is less than 500 nm.

[0023] In a fifth aspect, the present invention provides a positive electrode sheet comprising the positive electrode material described in the third aspect or a positive electrode material prepared by the preparation method described in the fourth aspect.

[0024] In a sixth aspect, the present invention provides a lithium-ion battery comprising the positive electrode sheet described in the fifth aspect.

[0025] The implementation of this invention has at least the following beneficial effects:

[0026] The NASICON-type solid electrolyte provided by this invention maximizes the electronic conductivity of the solid electrolyte by introducing transition metal elements and limiting the proportion of transition metal elements, giving the solid electrolyte dual conduction properties of lithium ion conduction and electron conduction; coating the solid electrolyte on the surface of the positive electrode material is beneficial to constructing a lithium ion-electron dual transport network, improving the reaction kinetics of ion / electron exchange, and improving rate performance and cycle performance while ensuring battery capacity. Attached Figure Description

[0027] Figure 1 These are XRD characterization diagrams of the solid electrolytes of Examples 1-4 and Comparative Example 1 of the present invention;

[0028] Figure 2 This is a SEM image of the nanoparticle powder in Example 1;

[0029] Figure 3 This is an SEM image of the nanoparticle powder in Example 2;

[0030] Figure 4 This is a SEM image of the nanoparticle powder in Example 3;

[0031] Figure 5 This is an SEM image of the nanoparticle powder in Example 4;

[0032] Figure 6 This is a SEM image of the nanoparticle powder in Comparative Example 1;

[0033] Figure 7 This is a SEM image of the cathode material in Example 1;

[0034] Figure 8 This is a SEM image of the cathode material in Example 2;

[0035] Figure 9 This is a SEM image of the cathode material in Example 3;

[0036] Figure 10 This is a SEM image of the cathode material in Example 4;

[0037] Figure 11 The image shows the SEM image of the cathode material in Comparative Example 1.

[0038] Figure 12 Here is a SEM image of the cathode material in Comparative Example 2;

[0039] Figure 13 This is a SEM image of the cathode material in Comparative Example 3. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0041] In a first aspect, the present invention provides a NASICON-type solid electrolyte, the chemical structural formula of which is: Li 1+x M 1 x Ti 2-x (PO4) y (M 2 O4) z Where 0 ≤ x ≤ 0.6, 1.5 ≤ z ≤ 4.5, 50% ≤ z / (y+z) ≤ 100%; M 1 Including at least one of Al, Y, Fe, Cr, Nb, and Zr; M 2 It includes at least one of V, Mo, W, and Nb.

[0042] The crystal structure of NASICON-type solid electrolytes mainly consists of an octahedral structure of TiO6 and a tetrahedral structure of PO4. The octahedral structure of TiO6 and the tetrahedral structure of PO4 are interconnected through shared O atoms, forming a 3D lithium-ion transport network. However, the PO4 tetrahedral structure is a non-metallic polyanion, which hinders electron transport. Existing technologies do not introduce M... 2 The NASICON-type solid electrolyte exhibits the behavior of a pure lithium-ion conductor (electronically insulated), but using this solid electrolyte to coat the positive electrode material would hinder charge transfer. This invention also introduces the metal element M. 1 M 2 , making M 1 Partial Ti substitution forms M 1 The O6 octahedral structure enables the transition metal M 2 The substitution of some P forms a covalent bond (M) with the transition metal oxygen. 2 O4 a- ), and replace part of PO4. 3- Chemical bonds, in this way, help to improve the electronic conductivity of solid electrolytes, giving them dual conduction properties of lithium-ion conduction and electronic conduction.

[0043] Where 50% ≤ z / (y+z) ≤ 100%, z / (y+z) refers to M 2 The proportion of P that can be replaced is determined by making 50% ≤ z / (y+z) ≤ 100%, that is, M. 2 The proportion of P replacement is not less than 50%, so as to maximize the electronic conductivity of the solid electrolyte.

[0044] According to the research of this invention, the NASICON-type solid electrolyte possesses dual conduction properties of lithium-ion conduction and electronic conduction. This is because, on the one hand, a transition metal element M is introduced at the phosphorus site. 2 Doping is beneficial for improving the electronic conductivity of solid electrolytes; on the other hand, by limiting M... 2 The proportion of P replaced is adjusted to maximize the electronic conductivity of the solid electrolyte, giving it dual conductivity properties of lithium-ion conduction and electronic conduction.

[0045] In this invention, in M 2 O4 a- In the middle, a is M 2 In some embodiments, the valence of the corresponding anion satisfies 3y + az = 9, where a = 2 or a = 3.

[0046] This invention does not limit the electronic conductivity or lithium-ion conductivity of the NASICON-type solid electrolyte. For example, in some embodiments, the electronic conductivity of the NASICON-type solid electrolyte is >10.-5 S / cm; and / or, the lithium-ion conductivity of NASICON-type solid electrolytes >10 -4 S / cm; and / or, the band gap of the NASICON-type solid electrolyte is no greater than 0.7 eV. Here, the electronic conductivity and lithium-ion conductivity of the NASICON-type solid electrolyte refer to the electronic conductivity and lithium-ion conductivity at room temperature (30°C); the band gap (energy band gap) is the result of first-principles calculations based on generalized density function theory. By limiting the band gap to no greater than 0.7 eV, electrons can easily transfer from the valence band to the conduction band, which is beneficial for electron conduction.

[0047] A second aspect of the present invention provides a method for preparing the NASICON-type solid electrolyte provided in the first aspect, comprising the following steps: mixing a lithium source, a titanium source, a phosphorus source, and providing M... 1 Compounds that provide M 2 The compounds were mixed and sintered to obtain a NASICON-type solid electrolyte.

[0048] The amount of each raw material can be adjusted according to the stoichiometric ratio. In some embodiments, the amount of lithium source added is 0.9 to 1.2 times the stoichiometric ratio, preferably 1.05 times.

[0049] This invention does not impose many limitations on the mixing method, and conventional methods in the art can be used. For example, the mixing method can be dry mixing of pure solid phases or wet mixing with the addition of solvent; wherein, the dry mixing method can be the mixing of commercial high mixers or plow mixers commonly used in the field of cathode material production processes, and the solvent for wet mixing can be common organic solvents such as ethanol, isopropanol, and methanol, and the equipment used for wet mixing can be common mature process equipment such as ball mills, sand mills, and mechanical stirring.

[0050] This invention does not impose excessive limitations on the specific details of the selection of raw materials. For example, the lithium source can be one or more combinations of Li₂CO₃, LiOH·H₂O, Li₃PO₄, and LiNO₃; the titanium source can be one or more combinations of TiO₂, titanium hydroxide, titanium chloride, and TiP₂O₇; the phosphorus source can be one or more combinations of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and TiP₂O₇; and M is provided. 1 Compounds that provide M 2 The compounds are selected based on the types of elements; for example, M is provided. 2 The compounds can be one or more of the following: Li3VO4, V2O5, V2O4, V2O3, WO2, WO3, tungstic acid, (NH4)2MoO4, Li2MoO4, H2MoO4, Nb2O5, lithium niobate, niobium oxalate, and ammonium niobium oxalate.

[0051] This invention does not impose excessive limitations on the preparation parameters of the sintering process, as long as the aforementioned solid electrolyte can be obtained. It should be noted that the sintering process can be a one-stage sintering or a two-stage sintering. In some embodiments, when the sintering process is a one-stage sintering, the sintering temperature is 650–1050°C, for example, a range of 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 1050°C, or any combination thereof, and the time is 2–10 hours, for example, 2 hours, 5 hours, 10 hours, or any combination thereof. The heating rate is 2–8°C / min.

[0052] In other embodiments, if the phosphorus source is ammonium dihydrogen phosphate or diammonium hydrogen phosphate, the sintering process is a two-stage sintering process, comprising a first sintering process and a second sintering process. The temperature of the first sintering process is 450–550°C, and the temperature of the second sintering process is 800–1000°C. In a specific implementation of the present invention, the first sintering process is performed first. The material after the first sintering is knocked off the sagger, ball-milled, and then subjected to the second sintering process to obtain a solid electrolyte.

[0053] A third aspect of the present invention provides a positive electrode material, comprising a positive electrode material substrate and a coating layer covering the surface of the positive electrode material substrate, wherein the material of the coating layer comprises a NASICON-type solid electrolyte provided in the first aspect or a NASICON-type solid electrolyte prepared by the preparation method provided in the second aspect.

[0054] Since the NASICON-type solid electrolyte possesses dual conduction properties of lithium-ion and electron conduction, the cathode material of this invention is beneficial for constructing a lithium-ion-electron dual transport network, improving the reaction kinetics of ion / electron exchange, and effectively enhancing rate performance and cycle performance while ensuring battery specific capacity.

[0055] The present invention does not limit the mass content of NASICON-type solid electrolyte in the cathode material. For example, in some embodiments, the mass percentage of NASICON-type solid electrolyte in the cathode material matrix is ​​0.01 to 5 wt%, such as 0.01%, 0.1%, 1%, 5%, or any combination thereof.

[0056] A fourth aspect of the present invention provides a method for preparing the positive electrode material provided in the third aspect, comprising the following steps: pulverizing a NASICON-type solid electrolyte to obtain nanoparticle powder; mixing the nanoparticle powder with a positive electrode material matrix and then annealing it to obtain the positive electrode material; or, mixing the nanoparticle powder with a dispersant to obtain a mixture, adding the positive electrode material matrix to the mixture, and then drying and annealing it to obtain the positive electrode material.

[0057] In this invention, NASICON-type solid electrolytes are pulverized into nanoparticles or nano-to-submicron particles through a pulverization process. This invention does not limit the specific type of pulverization process; it can be sand milling, high-energy ball milling, or pulverization using an air jet mill.

[0058] The mixing process of nanoparticle powder with the cathode material matrix can be carried out using solid-phase dry mixing or wet methods. For example, the nanoparticle powder and the cathode material matrix can be mixed in a high-speed mixer or a plow mixer; or, the powder and a dispersant can be mixed and ball-milled or sand-milled to obtain a slurry. The cathode material matrix is ​​then added to the slurry. The dispersant can be at least one of water, ethanol, N-methylpyrrolidone (NMP), and isopropanol, wherein the mass ratio of dispersant to powder is controlled at (0.1–10):1. The cathode material matrix is ​​then added, and the mixture is stirred for 1–20 minutes at a stirring intensity of 150–500 r / min. After filtration and vacuum drying, a block material is obtained. The block material is then annealed to obtain the cathode material. The drying temperature is 80–150 °C; the solid content of the NASICON-type solid electrolyte in the mixture is 1–60 wt%.

[0059] In some embodiments, the annealing treatment is carried out in an oxygen-containing atmosphere, the annealing temperature is 250–800°C, and the time is 2–15 h; and / or, the D50 of the nanoparticle powder is less than 500 nm.

[0060] In a fifth aspect, the present invention provides a positive electrode sheet comprising the positive electrode material provided in the third aspect or the positive electrode material prepared by the preparation method provided in the fourth aspect.

[0061] The positive electrode sheet of the present invention can also be prepared using conventional techniques in the art. Specifically, the above-mentioned positive electrode material, conductive agent, and binder can be uniformly dispersed in a solvent to obtain a positive electrode active layer slurry. Then, the positive electrode active layer slurry is coated on at least one functional surface of the positive electrode current collector, and after drying, the positive electrode sheet of the present invention can be obtained.

[0062] This invention does not specifically limit the types of conductive agents and adhesives. The conductive agents, adhesives and other components can all be conventional substances in the field. For example, the conductive agent can be selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite and graphene, and the adhesive can be selected from one or more of polyvinylidene fluoride (PVDF), acrylic modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber and styrene-acrylic rubber.

[0063] The present invention does not specifically limit the coating method, and any coating method such as gravure coating, extrusion coating, spraying, screen printing, etc. can be used to achieve the coating of the positive electrode active layer slurry.

[0064] In a sixth aspect, the present invention provides a lithium-ion battery, comprising the positive electrode sheet provided in the fifth aspect. In addition to the positive electrode sheet, the lithium-ion battery of the present invention also includes a separator, a negative electrode sheet, and an electrolyte. The composition of the negative electrode sheet can refer to conventional negative electrode sheets in the art, and the separator can also be a separator conventionally used in the art, such as a PP film or a PE film.

[0065] The lithium-ion battery of the present invention can be prepared using conventional methods in the art. Specifically, the positive electrode, separator and negative electrode can be stacked in sequence, and the cell can be obtained by stacking or winding process. Then, the lithium-ion battery can be obtained by baking, liquid injection, formation and packaging.

[0066] The present invention will be further described below through specific embodiments and comparative examples.

[0067] Example 1

[0068] I. Preparation of NASICON-type solid electrolytes

[0069] (1) According to Li 1.3 Al 0.3 Ti 1.7 (PO4) 1.2 (VO4) 1.8 The stoichiometric ratios of LiOH·H2O (weighed as 5% excess) were 57.28 g, TiO2 was 135.78 g, V2O5 was 163.69 g, Al2O3 was 15.29 g, and NH4H2PO4 was 138.03 g. Alcohol was added and ball-milled at 300 r / min for 6 h, with the ball-to-material ratio controlled at 1.5:1. After drying, the precursor material was obtained.

[0070] (2) Place the precursor material from step (1) in a muffle furnace, set the heating rate to 3℃ / min up to 500℃ (first firing temperature), and hold for 2 hours to obtain a hardened process material after removing water and NH3. After ball milling, put it back into the muffle furnace, set the heating rate to 3℃ / min up to 800℃ (second firing temperature), and hold for 5 hours to obtain a white NASICON-type solid electrolyte Li. 1.3 Al 0.3 Ti 1.7 (PO4) 1.2 (VO4) 1.8 It was named LATPV0.6.

[0071] II. Preparation of Cathode Materials

[0072] (1) The LATPV0.6 powder was milled with anhydrous ethanol as the dispersion medium. The milling parameters were 2500 r / min for 60 min to obtain LATPV0.6 nano slurry.

[0073] (2) Wet coating was carried out using LATPV0.6 nano-slurry as the coating material. Specifically, 1.0 g of net LATPV0.6 solid content was weighed and diluted evenly dispersed in 200 g of deionized water to obtain LATPV0.6 nano-slurry. 200 g of single-crystal high-nickel ternary cathode material LiNi was added. 0.83 Co 0.12 Mn 0.05 O2 powder was stirred at a stirring speed of 200 r / min for 10 min, and then vacuum filtered to obtain a filter cake. After crushing the filter cake, it was dried under vacuum at 120℃ for 12 h to obtain a composite powder.

[0074] (3) The composite powder from step (2) is put into a chamber atmosphere furnace, the atmosphere is controlled to be pure oxygen (oxygen partial pressure > 92%), the heating rate is 2℃ / min to 550℃, and the temperature is held for 10h to obtain a positive electrode material coated with solid electrolyte LATPV0.6, denoted as LATPV0.6@Ni83.

[0075] Example 2

[0076] I. Preparation of NASICON-type solid electrolytes

[0077] (1) According to Li 1.3 Al 0.3 Ti 1.7 The stoichiometric ratio of (PO4)(WO4)3 is as follows: LiOH·H2O (measured as 5% excess): 57.28g, TiO2: 95.84g, WO3: 695.52g, Al2O3: 15.29g, TiP2O7: 110.91g. Alcohol is added and ball-milled at 300r / min for 6h, controlling the ball-to-material ratio at 1.5:1. After drying, the precursor material is obtained.

[0078] (2) Place the precursor material from step (1) in a muffle furnace, set the heating rate to 3℃ / min to 950℃, and hold for 10h to obtain the grayish-white NASICON-type solid electrolyte Li. 1.3 Al 0.3 Ti 1.7 (PO4)(WO4)3, named LATPW0.75.

[0079] II. Preparation of Cathode Materials

[0080] (1) The LATPW0.75 powder was milled with anhydrous ethanol as the dispersion medium. The milling parameters were 2500 r / min for 60 min to obtain LATPW0.75 nano slurry. The LATPW nano slurry was dried by evaporating anhydrous ethanol to obtain LATPW0.75 nano dry powder.

[0081] (2) Dry coating was carried out using LATPW0.75 nano dry powder as the coating material. Specifically, 2g of LATPW0.75 nano dry powder was weighed and added to 200g of LiNi 0.9 Co 0.05 Mn 0.05 In O2 polycrystalline secondary spherical ternary cathode material powder, the mixture was ball-milled at 250 r / min for 6 h with a ball-to-material ratio of 1:1 to obtain composite cathode powder.

[0082] (3) The composite powder from step (2) is put into a chamber atmosphere furnace, the atmosphere is controlled to be pure oxygen (oxygen partial pressure > 95%), the heating rate is 2℃ / min to 550℃, and the temperature is held for 10h to obtain a positive electrode material coated with solid electrolyte LATPW0.75, denoted as LATPW0.75@Ni90.

[0083] Example 3

[0084] I. Preparation of NASICON-type solid electrolytes

[0085] (1) According to Li 1.3 Al 0.3 Ti 1.7 (PO4) 0.787 (MoO4) 3.32 Stoichiometric weighing was performed on the following components: LiOH·H2O (5% excess): 57.28g, TiO2: 104.35g, MoO3: 477.88g, Al2O3: 15.29g, and TiP2O7: 87.28g. Alcohol was added and the mixture was ball-milled at 300 r / min for 6 h, maintaining a ball-to-material ratio of 1.5:1. After drying, the precursor material was obtained.

[0086] (2) Place the precursor material from step (1) in a muffle furnace, set the heating rate to 3℃ / min to 880℃, and hold for 8 hours to obtain a grayish-white NASICON-type solid electrolyte Li. 1.3 Al 0.3 Ti 1.7 (PO4) 0.787 (MoO4) 3.32 It was named LATPM0.81.

[0087] II. Preparation of Cathode Materials

[0088] (1) The LATPM0.81 powder was milled with anhydrous ethanol as the dispersion medium. The milling parameters were 2500 r / min for 60 min to obtain LATPM0.81 nano slurry. The LATPM0.81 nano slurry was dried by evaporating anhydrous ethanol to obtain LATPM0.81 nano dry powder.

[0089] (2) Dry coating was carried out using LATPM0.81 nano dry powder as the coating material. Specifically, 1g of LATPM0.81 nano dry powder was weighed and added to 200g of LiNi 0.6 Co 0.2 Mn 0.2 O2 single crystal nickel ternary cathode powder was ball-milled at 250 r / min for 6 h with a ball-to-powder ratio of 1:1 to obtain composite cathode powder.

[0090] (3) The composite cathode powder from step (2) is put into a chamber atmosphere furnace, the atmosphere is controlled to be pure oxygen (oxygen partial pressure > 95%), the heating rate is 2℃ / min to 550℃, and the temperature is held for 10h to obtain cathode material coated with solid electrolyte LATPM0.81, denoted as LATPM0.81@Ni60.

[0091] Example 4

[0092] I. Preparation of NASICON-type solid electrolytes

[0093] The preparation method is basically the same as that in Example 1, except that it follows the Li 1.3 Al 0.3 Ti 1.7 (PO4) 0.9 (NbO4) 2.1 The stoichiometric proportions of LiOH·H₂O (weighed as 5% excess) were: 57.28 g, TiO₂: 135.78 g, Nb₂O₅: 279.11 g, Al₂O₃: 15.29 g, and ammonium dihydrogen phosphate: 103.52 g. Under unchanged conditions, the NASICON-type solid electrolyte Li₂ was obtained. 1.3 Al 0.3 Ti 1.7 (PO4) 1.5 (NbO4) 1.5 It was named LATPN0.7.

[0094] II. Preparation of Cathode Materials

[0095] The preparation method is basically the same as that in Example 1, except that the LATPV0.6 nano-slurry in Example 1 is replaced with LATPN0.7 powder in this example, while other conditions remain unchanged, to obtain LATPN0.7@Ni83.

[0096] Example 5

[0097] I. Preparation of NASICON-type solid electrolytes

[0098] The preparation method is basically the same as that in Example 2, except that it follows the Li 1.3 Al 0.3 Ti 1.7 (PO4) 9 / 11 (WO4) 36 / 11 The stoichiometric proportions of LiOH·H₂O (weighed as 5% excess) were: 57.28 g, TiO₂: 103.1 g, WO₃: 758.75 g, Al₂O₃: 15.29 g, and TiP₂O₇: 90.74 g. Under unchanged conditions, the NASICON-type solid electrolyte Li₂ was obtained. 1.3 Al 0.3 Ti 1.7 (PO4) 9 / 11 (WO4) 36 / 11 It was named LATPW0.8.

[0099] II. Preparation of Cathode Materials

[0100] The preparation method is basically the same as that in Example 2, except that the LATPW0.75 powder in Example 2 is replaced with the LATPW0.8 powder in this example, while other conditions remain unchanged, to obtain LATPW0.8@Ni90.

[0101] Example 6

[0102] I. Preparation of NASICON-type solid electrolytes

[0103] The preparation method is basically the same as that in Example 2, except that it follows the Li 1.3 Al 0.3 Ti 1.7 (WO4) 4.5 The stoichiometric proportions of LiOH·H₂O (weighed as 5% excess) were: 57.28 g, TiO₂: 135.779 g, WO₃: 1043.28 g, and Al₂O₃: 15.29 g. Under unchanged conditions, the NASICON-type solid electrolyte Li₂ was obtained. 1.3 Al 0.3 Ti 1.7 (WO4) 4.5 It was named LATW1.0.

[0104] II. Preparation of Cathode Materials

[0105] The preparation method is basically the same as that in Example 2, except that the LATPW0.75 powder in Example 2 is replaced with the LATW1.0 powder in this example, while other conditions remain unchanged, to obtain LATW1.0@Ni90.

[0106] Example 7

[0107] I. Preparation of NASICON-type solid electrolytes

[0108] The preparation method is basically the same as that in Example 3, except that it is prepared according to Li 1.3 Al 0.3 Ti 1.7 (PO4) 9 / 11 (MoO4) 36 / 11 The stoichiometric proportions of LiOH·H₂O (weighed as 5% excess) were: 57.28 g, TiO₂: 103.1 g, MoO₃: 471.08 g, Al₂O₃: 15.29 g, and TiP₂O₇: 90.74 g. Under unchanged conditions, the NASICON-type solid electrolyte Li₂ was obtained. 1.3 Al 0.3 Ti 1.7 (PO4) 9 / 11 (MoO4) 36 / 11 It was named LATPM0.8.

[0109] II. Preparation of Cathode Materials

[0110] The preparation method is basically the same as that in Example 3, except that the LATPM0.81 powder in Example 3 is replaced with the LATPM0.8 powder in this example, and other conditions remain unchanged to obtain LATPM0.8@Ni60.

[0111] Example 8

[0112] I. Preparation of NASICON-type solid electrolytes

[0113] The preparation method is basically the same as in Example 1, except that: according to Li 1.3 Fe 0.1 Cr 0.2 Ti 1.7 (PO4) 1.2 (VO4) 1.8 The stoichiometric proportions of LiOH·H₂O (weighed as 5% excess) were: 57.28 g, TiO₂: 135.78 g, ammonium dihydrogen phosphate: 138.03 g, V₂O₅: 163.69 g, Cr(NO₃)₃·9H₂O: 80.03 g, and Fe(NO₃)₃·9H₂O: 40.4 g. Other process conditions remained unchanged, with the secondary calcination temperature at 935℃ and the holding time at 24 h, yielding M. 1Bimetallic element-doped NASICON-type electrolyte Li 1.3 Fe 0.1 Cr 0.2 Ti 1.7 (PO4) 1.2 (VO4) 1.8 .

[0114] Example 9

[0115] I. Preparation of NASICON-type solid electrolytes

[0116] The preparation method is basically the same as in Example 1, except that: according to Li 1.3 Al 0.1 Y 0.2 Ti 1.7 (PO4) 1.2 (VO4) 1.8 The stoichiometric proportions of LiOH·H2O (weighed as 5% excess) were: 57.28 g, TiO2: 135.78 g, ammonium dihydrogen phosphate: 138.03 g, V2O5: 163.69 g, Al2O3: 10.2 g, and Y2O3: 45.16 g. Other processes remained unchanged, with the secondary calcination temperature at 860℃ and the holding time at 10 h, yielding M. 1 Bimetallic element-doped NASICON-type electrolyte Li 1.3 Al 0.1 Y 0.2 Ti 1.7 (PO4) 1.2 (VO4) 1.8 .

[0117] Example 10

[0118] I. Preparation of NASICON-type solid electrolytes

[0119] The preparation method is basically the same as in Example 2, except that: according to Li 1.3 Al 0.1 Y 0.2 Ti 1.7 The stoichiometric proportions of (PO4)(WO4)3 were as follows: LiOH·H2O (5% excess): 57.28 g, TiO2: 95.84 g, TiP2O7: 110.91 g, WO3: 695.52 g, Al2O3: 10.2 g, Y2O3: 45.16 g. Other process conditions remained unchanged, with the second calcination temperature at 860℃ and the holding time at 12 h, yielding M. 1 Bimetallic element-doped NASICON-type electrolyte Li 1.3 Al 0.1 Y 0.2 Ti 1.7(PO4)(WO4)3.

[0120] Example 11

[0121] I. Preparation of NASICON-type solid electrolytes

[0122] The preparation method is basically the same as in Example 3, except that: according to Li 1.3 Al 0.1 Y 0.2 Ti 1.7 (PO4) 0.787 (MoO4) 3.32 The stoichiometric proportions of LiOH·H₂O (weighed as 5% excess) were: 57.28 g, TiO₂: 104.35 g, TiP₂O₇: 87.28 g, MoO₃: 477.88 g, Al₂O₃: 10.2 g, and Y₂O₃: 45.16 g. Other process conditions remained unchanged, with the second calcination temperature at 860℃ and the holding time at 10 h, yielding M. 1 Bimetallic element-doped NASICON-type electrolyte Li 1.3 Al 0.1 Y 0.2 Ti 1.7 (PO4) 0.787 (MoO4) 3.32 .

[0123] Example 12

[0124] I. Preparation of NASICON-type solid electrolytes

[0125] The preparation method is basically the same as in Example 4, except that: according to Li 1.3 Zr 0.1 Nb 0.1 Ti 1.7 (PO4) 0.9 (NbO4) 2.1 The stoichiometric ratios were as follows: LiOH·H₂O (weighed as 5% excess): 57.28 g, TiO₂: 135.78 g, ammonium dihydrogen phosphate: 103.52 g, Nb₂O₅: 279.11 g, Al₂O₃: 10.2 g, Y₂O₃: 45.16 g. Other process conditions remained unchanged, with the secondary calcination temperature at 880℃ and the holding time at 12 h, yielding M. 1 Bimetallic element-doped NASICON-type electrolyte Li 1.3 Al 0.1 Y 0.2 Ti 1.7 (PO4) 0.9 (NbO4) 2.1 .

[0126] Comparative Example 1

[0127] I. Preparation of Solid Electrolytes

[0128] The NASICON-type solid electrolyte Li in this comparative example 1.3 Al 0.3 Ti 1.7 The preparation method of (PO4)3 includes the following steps:

[0129] (1) Weigh LiOH·H2O (measured as 5% excess) according to the stoichiometric ratio: 57.28g, TiO2: 135.78g, NH4H2PO4: 345.08g, Al2O3: 15.29g, and mix them at 300r / min for 6h using a ball milling process for wet mixing of alcohol, controlling the ball-to-material ratio to be 1.5:1. After drying, the precursor material is obtained.

[0130] (2) The white precursor powder mixed in (1) was placed in a muffle furnace, and the heating rate was set to 3℃ / min. The temperature was raised to 500℃ and held for 2 hours to obtain a grayish-white hard material. The grayish-white hard material was knocked off the sagger and ball-milled to obtain a grayish-white pre-calcined fine powder. The pre-calcined fine powder was placed in a muffle furnace, and the temperature was raised to 800℃ at a heating rate of 3℃ / min. After holding for 5 hours, pure white Li was obtained. 1.3 Al 0.3 Ti 1.7 The (PO4)3 solid electrolyte material is named LATP.

[0131] II. Preparation of Cathode Materials

[0132] (1) The LATP powder was milled in anhydrous ethanol as the dispersion medium. The milling parameters were 2500 r / min for 60 min to obtain LATP nano slurry.

[0133] (2) Wet coating was carried out using LATP nano-slurry as the coating material. Specifically, LATP nano-slurry with a net LATP solid content of 1.0 g was weighed and diluted and evenly dispersed in 200 g of deionized water, and 200 g of single-crystal high-nickel ternary cathode material LiNi was added. 0.83 Co 0.12 Mn 0.05 O2 powder was stirred at a stirring rate of 200 r / min for 10 min, and then vacuum filtered to obtain a filter cake. After crushing the filter cake, it was dried under vacuum at 120℃ for 12 h to obtain a composite powder.

[0134] (3) The composite cathode powder from step (2) is put into a chamber atmosphere furnace, the atmosphere is controlled to be pure oxygen (oxygen partial pressure > 92%), the heating rate is 2℃ / min to 550℃, and the temperature is held for 10h to obtain a cathode material coated with solid electrolyte LATP, denoted as LATP@Ni83.

[0135] Comparative Example 2

[0136] I. Preparation of Solid Electrolytes

[0137] Consistent with the solid electrolyte LATP of Comparative Example 1.

[0138] II. Preparation of Cathode Materials

[0139] The preparation method is basically the same as that in Example 2, except that the LATPW0.75 powder in Example 2 is replaced with the LATP powder in this comparative example, while other conditions remain unchanged, to obtain LATP@Ni90.

[0140] Comparative Example 3

[0141] I. Preparation of Solid Electrolytes

[0142] Consistent with the solid electrolyte LATP of Comparative Example 1.

[0143] II. Preparation of Cathode Materials

[0144] The preparation method is basically the same as that in Example 3, except that the LATPMo0.81 powder in Example 3 is replaced with the LATP powder in this comparative example, while other conditions remain unchanged, to obtain LATP@Ni60.

[0145] Comparative Example 4

[0146] I. Preparation of Solid Electrolytes

[0147] The preparation method is basically the same as that in Example 1, except that it follows the Li 1.3 Al 0.3 Ti 1.7 (PO4) 2.1 (VO4) 0.9 The stoichiometric proportions of LiOH·H₂O (weighed as 5% excess) were: 57.28 g, TiO₂: 135.78 g, V₂O₅: 81.846 g, Al₂O₃: 15.29 g, and NH₄H₂PO₄: 241.56 g. Under otherwise unchanged conditions, the NASICON-type solid electrolyte Li₂ was obtained. 1.3 Al 0.3 Ti 1.7 (PO4) 2.1 (VO4) 0.9 It was named LATPV0.3.

[0148] II. Preparation of Cathode Materials

[0149] The preparation method is basically the same as that in Example 1, except that the LATPV0.6 nano-slurry in Example 1 is replaced with the LATPV0.3 nano-slurry in this example, while other conditions remain unchanged, to obtain LATPV0.3@Ni83.

[0150] Comparative Example 5

[0151] I. Preparation of Solid Electrolytes

[0152] The preparation method is basically the same as that in Example 2, except that it follows the Li 1.3 Al 0.3 Ti 1.7 (PO4) 7 / 3 The stoichiometric proportions of LiOH·H2O (weighed as 5% excess) were: 57.28 g, TiO2: 42.6 g, WO3: 231.84 g, Al2O3: 15.29 g, and TiP2O7: 258.78 g. Under otherwise unchanged conditions, the NASICON-type solid electrolyte Li was obtained. 1.3 Al 0.3 Ti 1.7 (PO4) 7 / 3 (WO4), named LATPW0.3.

[0153] II. Preparation of Cathode Materials

[0154] The preparation method is basically the same as that in Example 2, except that the LATPW0.75 powder in Example 2 is replaced with the LATPW0.3 powder in this example, while other conditions remain unchanged, to obtain LATPW0.3@Ni90.

[0155] Comparative Example 6

[0156] I. Preparation of NASICON-type solid electrolytes

[0157] The preparation method is basically the same as that in Example 3, except that it is prepared according to Li 1.3 Al 0.3 Ti 1.7 (PO4) 7 / 3 The stoichiometric proportions of LiOH·H2O (weighed as 5% excess) were: 57.28 g, TiO2: 42.6 g, MoO3: 143.94 g, Al2O3: 15.29 g, and TiP2O7: 258.78 g. Under unchanged conditions, the NASICON-type solid electrolyte Li was obtained. 1.3 Al 0.3 Ti 1.7 (PO4) 7 / 3(MoO4) was named LATPM0.3.

[0158] II. Preparation of Cathode Materials

[0159] The preparation method is basically the same as that in Example 3, except that the LATPM0.81 powder in Example 3 is replaced with the LATPM0.3 powder in this example, while other conditions remain unchanged, to obtain LATPM0.3@Ni60.

[0160] Comparative Example 7

[0161] I. Preparation of NASICON-type solid electrolytes

[0162] The preparation method is basically the same as that in Example 3, except that it is prepared according to Li 1.3 Al 0.3 Ti 1.7 (PO4) 2.1 (NbO4) 0.9 The stoichiometric proportions of LiOH·H₂O (weighed as 5% excess) were: 57.28 g, TiO₂: 135.78 g, Nb₂O₅: 119.62 g, Al₂O₃: 15.29 g, and ammonium dihydrogen phosphate: 241.56 g. Under unchanged conditions, the NASICON-type solid electrolyte Li₂ was obtained. 1.3 Al 0.3 Ti 1.7 (PO4) 2.1 (NbO4) 0.9 It was named LATPN0.3.

[0163] II. Preparation of Cathode Materials

[0164] The preparation method is basically the same as that in Example 4, except that the LATPN0.7 powder in Example 4 is replaced with the LATPN0.3 powder in this example, while other conditions remain unchanged, to obtain LATPN0.3@Ni83.

[0165] Comparative Example 8

[0166] I. Preparation of Solid Electrolytes

[0167] The preparation method of the NASICON-type solid electrolyte LiTi2(PO4)3 in this comparative example includes the following steps:

[0168] According to the stoichiometric ratio of LiTi2(PO4)3, 44.06 g of LiOH·H2O, 345.08 g of ammonium dihydrogen phosphate, and 159.74 g of TiO2 were weighed and placed in a muffle furnace. The heating rate was set to 3℃ / min, and the temperature was raised to 500℃. After holding at this temperature for 2 hours, an intermediate material was obtained. The intermediate material was then broken off from the sagger and ball-milled to obtain a pre-calcined fine powder. The pre-calcined fine powder was placed in a muffle furnace and heated to 880℃ at a heating rate of 3℃ / min. After holding at this temperature for 30 hours, the LiTi2(PO4)3 solid electrolyte material was obtained.

[0169] Comparative Example 9

[0170] I. Preparation of Solid Electrolytes

[0171] The NASICON-type solid electrolyte Li in this comparative example 1.3 Fe 0.1 Cr 0.2 Ti 1.7 The preparation method of (PO4)3(LFCTP) includes the following steps:

[0172] According to Li 1.3 Fe 0.1 Cr 0.2 Ti 1.7 Weigh out LiOH·H2O (5% excess), ammonium dihydrogen phosphate, TiO2, Cr(NO3)3·9H2O, and Fe(NO3)3·9H2O according to the stoichiometric ratio. Place them in a muffle furnace, set the heating rate to 3℃ / min, heat to 500℃, and hold for 2 hours to obtain intermediate material. Remove the intermediate material from the crucible, ball mill it to obtain pre-calcined fine powder. Place the pre-calcined fine powder in a muffle furnace, heat to 880℃ at a heating rate of 3℃ / min, and hold for 30 hours to obtain Li. 1.3 Fe 0.1 Cr 0.2 Ti 1.7 (PO4)3 solid electrolyte material.

[0173] Comparative Example 10

[0174] I. Preparation of Solid Electrolytes

[0175] The NASICON-type solid electrolyte Li in this comparative example 1.3 Zr 0.1 Nb 0.1 Ti 1.7 The preparation method of (PO4)3(LZNTP) includes the following steps:

[0176] According to Li 1.3 Zr 0.1 Nb 0.1 Ti1.7 (PO4)3 was stoichiometrically weighed, and LiOH·H2O (5% excess), ammonium dihydrogen phosphate, TiO2, zirconium dioxide, and Nb2O5 were placed in a muffle furnace. The temperature was raised to 500℃ at a rate of 3℃ / min and held for 2 hours to obtain an intermediate material. The intermediate material was then removed from the crucible and ball-milled to obtain a pre-calcined fine powder. This pre-calcined fine powder was placed in a muffle furnace and heated to 910℃ at a rate of 3℃ / min, held for 30 hours to obtain Li. 1.3 Zr 0.1 Nb 0.1 Ti 1.7 (PO4)3 solid electrolyte material.

[0177] Comparative Example 11

[0178] I. Preparation of Solid Electrolytes

[0179] The NASICON-type solid electrolyte Li in this comparative example 1.3 Al 0.1 Y 0.2 Ti 1.7 The preparation method of (PO4)3(LAYTP) includes the following steps:

[0180] According to Li 1.3 Al 0.1 Y 0.2 Ti 1.7 (PO4)3 is stoichiometrically weighed, and LiOH·H2O (5% excess), ammonium dihydrogen phosphate, TiO2, Al2O3, and Y2O3 are placed in a muffle furnace. The heating rate is set to 3℃ / min, and the temperature is increased to 500℃. After holding at this temperature for 2 hours, an intermediate material is obtained. The intermediate material is then removed from the crucible and ball-milled to obtain a pre-calcined fine powder. The pre-calcined fine powder is placed in a muffle furnace and heated to 850℃ at a heating rate of 3℃ / min. After holding at this temperature for 30 hours, Li2O3 is obtained. 1.3 Al 0.1 Y 0.2 Ti 1.7 (PO4)3 solid electrolyte material.

[0181] Test case

[0182] 1. The solid electrolytes of Examples 1-4 and Comparative Example 1 were used as samples, and XRD characterization was performed on the samples. The results are shown in the figure. Figure 1 The XRD phase comparison (PDF:35-0754) showed no obvious impurity phase peaks, and the refinement results showed that the phase purity was above 99%.

[0183] The LATPV nanopowder from Example 1, the LATPW nanopowder from Example 2, the LATPMo nanopowder from Example 3, the LATPN nanopowder from Example 4, and the LATP nanopowder from Comparative Example 1 (wherein, the nanopowders of the examples and the comparative example were obtained by drying nano-slurry) were used as nanoparticle powder samples and characterized by a Malvern laser particle size analyzer and electron microscopy. The results are shown in Table 1 and 2. Figures 2 to 6 The results show that the particle size D50 of the nanoparticles in the examples and comparative examples is <200 nm, and they are uniformly dispersed. Electron microscopy was used to characterize the cathode materials in Examples 1-4 and Comparative Examples 1-3, and the results are shown in [Figure number missing]. Figures 7 to 13 .

[0184] 2. Conductivity test

[0185] Electrolyte sheets were prepared using a hot-pressing sintering method. The intermediate hard material or precursor material from the examples and the intermediate hard process material or precursor material from the comparative examples were used as samples for conductivity testing. The specific method is as follows: the sample was pulverized, placed into a mold, and first pressed into a sheet using a tablet press. Then, it was sintered at 800℃~1000℃ in air for 5~15 hours to obtain the electrolyte sheet. After sintering, the obtained electrolyte sheet was cut and polished into a circular sheet with a diameter of 10mm and a thickness of 1mm. Silver electrodes were deposited on both sides of the electrolyte sheet using magnetron sputtering technology, and the lithium-ion conductivity and electronic conductivity were tested. The sintering temperature of the electrolyte mother sheet in the examples and the comparative examples refers to the corresponding second sintering temperature, and the holding time refers to the corresponding holding duration.

[0186] The test results are shown in Tables 2 and 3.

[0187] 3. Theoretical calculation of band gap width

[0188] The bandgap was theoretically calculated using the NASICON-type solid electrolytes of Examples 1-3 and the solid electrolyte of Comparative Example 1 as samples.

[0189] The Vienna Ab initio Simulation Package (VASP) software with projected augmented wave pseudopotentials was used for generalized density functional theory calculations. The interaction between the valence electrons and ionic cores of the generalized gradient approximation (GGA) functional (PBE, Perdew-Burke-Ernzerhof) was described by a plane-wave mode-conserved pseudopotential, with a plane-wave cutoff energy of 500 eV. A 2×2×1 k-point grid was selected in the Brillouin zone using the Monkhorst-Pack method. During optimization, the energy convergence accuracy of a single atom was 10⁻⁶. -6 eV, the interatomic forces do not exceed When convergence is achieved, the parameter is considered to be 4.25 eV. The Hubbard parameter Ueff = 4.25 eV is introduced into the M2-xd state of the redox-oriented transition metal to correct the incomplete negation of the GGA self-interaction value. Simultaneously, to avoid interlayer interactions introduced by the periodic calculation method in the studied monolayer model, an addition of at least [value missing] eV is applied along the z-axis. The vacuum layer.

[0190] The calculation results of the band gap are shown in Table 2.

[0191] 4. Cyclic performance test

[0192] The positive electrode material, conductive carbon black Super P, and binder PVDF solution were weighed and mixed according to a mass ratio of 96:2:2. The mixture was then stirred in a planetary mixer until homogeneous. The mixture was coated onto an aluminum foil current collector and dried in an oven at 120°C for 2 hours. The resulting sheets were sliced ​​and compacted to obtain the corresponding positive electrode plates. Lithium metal was selected as the negative electrode, and the positive electrode loading was controlled at 15±1 mg / cm³. 2 They were assembled into button batteries in a glove box filled with argon gas.

[0193] The battery cycle performance test voltage range is 2.5-4.25V, the test rate is 1C, the initial discharge specific capacity test rate is 0.2C, and the battery cycle capacity retention is compared with the capacity values ​​after 200, 300 and 350 cycles.

[0194] The test results are shown in Table 4.

[0195] Table 1

[0196] Group D50(μm) D10(μm) D90(μm) <![CDATA[D MAX (μm)]]> <![CDATA[D MIN (μm)]]> Example 1 0.11 0.05 0.25 0.76 0.02 Example 2 0.11 0.05 0.26 0.76 0.02 Example 3 0.12 0.05 0.26 0.67 0.02 Example 4 0.11 0.06 0.26 0.73 0.02 Comparative Example 1 0.11 0.05 0.25 0.76 0.02

[0197] Table 2

[0198] Group Lithium-ion conductivity (mS / cm) Electron conductivity (mS / cm) Bandwidth gap (eV) Example 1 <![CDATA[5.29×10 -4 ]]> <![CDATA[1.87×10 -5 ]]> 0.608 Example 2 <![CDATA[3.31×10 -4 ]]> <![CDATA[9.44×10 -4 ]]> 0.269 Example 3 <![CDATA[4.61×10 -4 ]]> <![CDATA[2.39×10 -3 ]]> 0.0933 Example 4 <![CDATA[6.002×10 -4 ]]> <![CDATA[5.28×10 -4 ]]> 0.4863 Example 5 <![CDATA[3.619×10 -4 ]]> <![CDATA[1.55×10 -5 ]]> 0.299 Example 6 <![CDATA[1.99×10 -4 ]]> <![CDATA[5.22×10 -2 ]]> -0.1262 Example 7 <![CDATA[2.965×10 -4 ]]> <![CDATA[2.11×10 -3 ]]> 0.119 Comparative Example 1 <![CDATA[4.21×10 -4 ]]> <![CDATA[3.94×10 -9 ]]> 2.67 Comparative Example 4 <![CDATA[4.6398×10 -4 ]]> <![CDATA[2.377×10 -7 ]]> 1.416 Comparative Example 5 <![CDATA[5.036×10 -4 ]]> <![CDATA[2.644×10 -8 ]]> 1.6754 Comparative Example 6 <![CDATA[4.889×10 -4 ]]> <![CDATA[1.413×10 -7 ]]> 1.5697 Comparative Example 7 <![CDATA[3.8563×10 -4 ]]> <![CDATA[2.0015×10 -7 ]]> 1.398

[0199] Table 3

[0200]

[0201]

[0202] Table 4

[0203]

[0204] As shown in Table 2, the NASICON-type solid electrolyte of this invention, through the introduction of the transition metal element M... 2 Replacement of the PO site in the Nasicon structure to form M 2The -O tetrahedral spacing structure alters the electronic structure, thereby improving the material's conductivity. The inventors, through research, believe that with M... 2 Taking Mo as an example, the 4d electron orbitals of Mo (Z=3.32) facilitate electron transfer because they help alter the conduction bands at the top and bottom of the valence band, thereby reducing the band gap. The reduced band gap makes it easier for electrons to transfer from the valence band to the conduction band, which is beneficial for electron conduction. This allows solid electrolytes, when used as a coating material on the surface of cathode materials, to achieve simultaneous electron-ion dual conduction, accelerating electrode reaction kinetics and thus improving the electrochemical performance of the battery. In some embodiments, the band gap is negative, indicating partial overlap between the valence and conduction bands. A negative band gap suggests conductive properties and strong electronic conductivity.

[0205] As shown in Table 4, the examples exhibit higher discharge specific capacity and first-time coulombic efficiency compared to the comparative examples, especially with superior rate performance. The inventors believe that the solid electrolyte of this invention, due to its smaller interfacial charge transfer, reduces surface polarization side reactions and achieves better long-cycle retention. Furthermore, as shown in Table 3, the metal doping at the Ti site in the LATP electrolyte mainly regulates lithium-ion conductivity, while the transition metal doping at the P site mainly enhances electronic conductivity. Based on the above analysis, the inventors believe that the doping at the Ti site primarily regulates lithium-ion conduction, while the high proportion of transition metal substitution at the P site mainly affects the enhanced electronic conductivity. Examples 1-4 demonstrate a relatively balanced NASICON-type LATP electrolyte material for cathode material coating, achieving both lithium-ion transport and electron network construction, resulting in significant improvements in electrical performance and supporting the data analysis conclusions in Table 4.

[0206] The preferred embodiments and experimental verifications of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. A NASICON-type solid electrolyte, characterized in that, The chemical structural formula of the NASICON-type solid electrolyte is: Li 1+x M 1 x Ti 2-x (PO4) y (M 2 O4) z Where 0 < x ≤ 0.6, 1.5 ≤ z ≤ 4.5, 70% ≤ z / (y + z) ≤ 100%; M 1 Including at least one of Al, Y, Fe, Cr, Nb, and Zr; M 2 Including at least one of V, Mo, W, and Nb, wherein M 1 Replacement portion Ti, the M 2 Replacement part P; The electronic conductivity of the NASICON-type solid electrolyte is >10. -5 S / cm; The lithium-ion conductivity of the NASICON-type solid electrolyte is >10. -4 S / cm; The band gap of the NASICON-type solid electrolyte is no greater than 0.7 eV.

2. A method for preparing the NASICON-type solid electrolyte according to claim 1, characterized in that, Includes the following steps: Lithium source, titanium source, phosphorus source, provide M 1 Compounds that provide M 2 The compounds were mixed and sintered to obtain a NASICON-type solid electrolyte.

3. The preparation method according to claim 2, characterized in that, The sintering process is a one-stage sintering, wherein the temperature of the one-stage sintering is 650~1050℃ and the time is 2~10h; or, The sintering process is a two-stage sintering process, which includes a first sintering process and a second sintering process. The temperature of the first sintering process is 450~550℃, and the temperature of the second sintering process is 800~1000℃.

4. A positive electrode material, characterized in that, It includes a positive electrode material matrix and a coating layer covering the surface of the positive electrode material matrix, wherein the material of the coating layer includes the NASICON type solid electrolyte as described in claim 1 or the NASICON type solid electrolyte prepared by the preparation method described in claim 2 or 3.

5. The positive electrode material according to claim 4, characterized in that, The NASICON-type solid electrolyte accounts for 0.01~5 wt% of the mass of the positive electrode material matrix.

6. A method for preparing the positive electrode material according to claim 4 or 5, characterized in that, Includes the following steps: The NASICON-type solid electrolyte is pulverized to obtain nanoparticle powder; the nanoparticle powder or a slurry formed from the nanoparticle powder is mixed with the positive electrode material matrix and then annealed to obtain the positive electrode material.

7. The preparation method according to claim 6, characterized in that, The annealing treatment is carried out in an oxygen-containing atmosphere at a temperature of 250–800°C for 2–15 hours; and / or, The D50 of the nanoparticle powder is less than 500 nm.

8. A positive electrode plate, characterized in that, The positive electrode sheet includes the positive electrode material as described in claim 4 or 5, or the positive electrode material prepared by the preparation method described in claim 6 or 7.

9. A lithium-ion battery, characterized in that, The lithium-ion battery includes the positive electrode sheet as described in claim 8.

Citation Information

Patent Citations

  • A modified high-specific-capacity, high-nickel ternary cathode material and its preparation method

    CN111600014B

  • Preparation method of coated modified nickel-rich lithium ion ternary positive electrode material and product of coated modified nickel-rich lithium ion ternary positive electrode material

    CN115425202A

  • Positive electrode material and preparation method thereof, positive plate, battery and electric device

    CN115513437A

  • LATP (Lithium Aluminum Titanium Phosphate) monocrystal high-voltage anode material and preparation method thereof

    CN107768632A

  • Preparation method and application of incombustible composite-based solid electrolyte membrane

    CN114583252A